Relationship between Virulence and Resistance among Gram-Negative Bacteria - Virginio Cepas; Sara M. Soto (Antibiotics, 2020)
Bacteria present in the human body are innocuous, providing beneficial functions, some of which are necessary for correct body function. However, other bacteria are able to colonize, invade, and cause damage to different tissues, and these are categorised as pathogens. These pathogenic bacteria possess several factors that enable them to be more virulent and cause infection. Bacteria have a great capacity to adapt to different niches and environmental conditions (presence of antibiotics, iron depletion, etc.). Antibiotic pressure has favoured the emergence and spread of antibiotic-resistant bacteria worldwide. Several studies have reported the presence of a relationship (both positive and negative, and both direct and indirect) between antimicrobial resistance and virulence among bacterial pathogens. This review studies the relationship among the most important Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) taking into account two points of view: (i) the effect the acquisition of resistance has on virulence, and (ii) co-selection of resistance and virulence. The relationship between resistance and virulence among bacteria depends on the bacterial species, the specific mechanisms of resistance and virulence, the ecological niche, and the host.